Design Golas for the Space Shuttle's Thermal Protection System - Sun Kyu Kim (Journal of Astronomy and Space Sciences, 1984)
The design of the reusable thermal protection system for the space shuttle orbiter using silica tile played one of key roles in the successful flight of the Columbia and subsequent space shuttles. The basic design goals for this thermal protection system were identified. Manufacturing procedures for the silica tile and the structure of the tile system were also described.